2012
DOI: 10.1002/ajhb.22296
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of variability of high sensitivity C‐reactive protein in lowland ecuador reveals no evidence of chronic low‐grade inflammation

Abstract: This study is the first to investigate CRP variability in a nonindustrialized, high infectious disease environment. It documents a pattern of variation over time that is distinct from prior research, with no evidence for chronic low-grade inflammation. These results may have substantial implications for research on inflammation and diseases of aging globally, as well as for scientific understandings of the regulation of inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
78
1
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 44 publications
7
78
1
1
Order By: Relevance
“…Similarly, older women in the Philippines (35-69 y) have higher median CRP at 0.9 mg/L, but this concentration is still substantially lower than 2.02 mg/L, the median CRP for older American women (51). Additionally, in lowland Ecuador, median CRP for adults ages 18-50 y is 0.5 mg/L, despite a prevalence of infectious disease that is even higher than the Philippines (52).…”
Section: Early Environments and The Eco-logics Of Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, older women in the Philippines (35-69 y) have higher median CRP at 0.9 mg/L, but this concentration is still substantially lower than 2.02 mg/L, the median CRP for older American women (51). Additionally, in lowland Ecuador, median CRP for adults ages 18-50 y is 0.5 mg/L, despite a prevalence of infectious disease that is even higher than the Philippines (52).…”
Section: Early Environments and The Eco-logics Of Inflammationmentioning
confidence: 99%
“…We sought to answer these questions by documenting the pattern of CRP variability in lowland Ecuador (52). We collected blood samples from 52 adults over four weekly intervals, and during this time, almost two-thirds of the participants reported at least one episode of infectious disease.…”
Section: Vaccine Responsiveness In Adolescence Predicts Crp In Youngmentioning
confidence: 99%
“…A failure to do this is regularly seen in highincome countries where persistently raised levels of C-reactive protein (CRP) are common (discussed in ref. 31). Persistently raised inflammatory mediators lead to increased risk of cardiovascular disease (32) and depression (27,33,34).…”
Section: Hygiene Hypothesis and The "Old Friends" Mechanismmentioning
confidence: 99%
“…Persistently raised inflammatory mediators lead to increased risk of cardiovascular disease (32) and depression (27,33,34). In contrast, a longitudinal study of adults in a rural low-income country where there is exposure to high microbial burdens in childhood showed that they were able to shut off the inflammatory response when there was no need for it (31). More work is needed to discover whether the same is true in other low-income settings, whether biomass or biodiversity was more important, and whether the effect was attributable to bacteria, fungi, protozoa, helminths, or other organisms.…”
Section: Hygiene Hypothesis and The "Old Friends" Mechanismmentioning
confidence: 99%
See 1 more Smart Citation